Transformasi UMKM Desa Pupus Melalui Inovasi Packaging Dan E-Catalog Dalam Branding Desa Wisata Dewi Cemara 2025 - Antisa Jose Line; Tri Wahyuni; Puteri Puspa Dewi; Ajeng Setia Dewi; Erwinda Devita Rahma Dhani (PT Mekar Research and Publishing, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in strengthening rural economies and promoting local potential. However, MSMEs in Pupus Village face challenges such as unattractive product packaging and limited use of digital marketing tools. Through the 2025 Community Service Program (KKN) of Universitas Muhammadiyah Ponorogo, students assisted local MSMEs by introducing packaging design innovations with local identity elements and developing an e-catalog for digital promotion. This program aimed to enhance product image, marketability, and competitiveness. The implementation produced positive results, as evidenced by the recognition achieved by Pupus MSMEs at the Dewi Cemara Festival 2025. These findings indicate that combining packaging innovation with product digitalization can effectively strengthen MSME branding, expand market reach, and support the development of creative economies within village-based tourism.